The fitness “working class” and its relationship with fitness equipment: a systematic review - Silvio Addolorato; Jerónimo García-Fernández; Leonor Gallardo; Jorge García-Unanue (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Fitness equipment nowadays represent something common in human beings daily life routines. For this reason, the number of sector professionals and human resources are quantitatively and significantly increasing worldwide. This paper provides a comprehensive systematic review of the current status of scientific research on field workers in relation to the usage of fitness products and resources. The performed thematic synthesis allowed to define and sort contents into three pyramidal categories and selected keywords offered about 49 articles that have been extensively analysed: (1) owners / directors; (2) personal trainers; and (3) instructors. Discussions of each category and all the existing relationships with fitness equipment are advanced and defined. Health and sport workers must recognise the relevant contribution of these stakeholders’ characteristics in the way to maximise the role of fitness equipment in promoting leisure and healthy habits inside societies. In addition, practitioners and researchers could take advantage in deepening knowledge and education on these kinds of resources. Due to the current importance of the sector, standardization and regulation of each fitness industry work category is ready to be strengthened also under these scientific to practice points of view.